Thai information technology customer loyalty perceptions: A structural equation model - Pongcharnchavalit, Surachet; Fongsuwan, Wanno (My University, 2015)
Customer loyalty is composed of many factors including customer expectations, perceived quality, perceived value, corporate image, customer satisfaction, customer trust/confidence, customer commitment and customer complaints. This study strove to investigate the influence of loyalty factors and the relationship with the Thai information technology product and service sector. Thai IGT investments were expected to grow 7.2% in 2014 over 2013 with 105,000 Wi-Fi hotspots being installed around the country. Study after study stresses the importance of ICT to a nation's prosperity, well-being and growth so the study's researchers undertook data analysis using both qualitative and quantitative research methods to examine how perceived product/service quality, customer perceived value and customer trust affect customer loyalty. The results of the study showed that the customer perception of information technology product service/quality had an indirect but positive effect on both customer trust and the perceived value of the product or service. They, in turn, had a direct effect on customer loyalty. The findings from this study foundthat information technology customers using product and/or services, regardless of the price focused on purchasing technology products with service after the sale. So, the perception of quality and the recognition of the value are necessary to provide customers with trust in the brand itself with leads to longer customer retention.
Keywords: Customer loyalty; Perceived product; Perceived value; Service quality; Trust